Appraising The Law of Wills in A Contract - Emad Mohammad Al Amaren; Rachma Indriyani (Fakultas Hukum Universitas Hang Tuah, 2019)
Contracts play a significant role in both economic and commercial transactions, whether internal contract within a national legal system of a State or contract with international nature due to there is more than one legal system would be involved. As a tool that runs international trade and a means of economic exchanges across the border, it can not be denied that many practitioners have high stakes and interest through a contract. The internationality of the contract may impose its subordination to a law other than the law of the judge, and may be subjected to the international substantive rules represented in the most common rules of international law or common principles of international trade rules. Therefore, the definition of the concept of an international contract is a critical issue for the consequences of this limitation. This study reckons the appraisal between domestic and international contract is crucial to do as well as the role of the will in internationalizing the contract.